Narratives of the Unspoken in Contemporary Irish Fiction Silences that Speak - Caneda-Cabrera, M. Teresa; Carregal-Romero, José (New Directions in Irish and Irish American Literature, 2023)
This Open access book is a collection of essays and offers an in-depth analysis of silence as an aesthetic practice and a textual strategy which paradoxically speaks of the unspoken nature of many inconvenient hidden truths of Irish society in the work of contemporary fiction writers. The study acknowledges Ireland's history of damaging silences and considers its legacies, but it also underscores how silence can serve as a valuable, even productive, means of expression. From a wide range of critical perspectives, the individual essays address, among other issues, the conspiracies of silence in Catholic Ireland, the silenced structural oppression of Celtic Tiger Ireland, the recovery of silenced stories/voices of the past and their examination in the present, as well as millennial disaffection and the silencing of vulnerability in today's neoliberal Ireland. The book 's attention to silence provides a rich vocabulary for understanding what unfolds in the quiet interstices of Irish writing from recent decades. This study also invokes the past to understand the present and, thus, demonstrates the continuities and discontinuities that define how silence operates in Irish culture. Grant FFI2017-84619-P AEI, ERDF, EU (INTRUTHS "Inconvenient Truths: Cultural Practices of Silence in Contemporary Irish Fiction") Funded by the Spanish Research Agency AEI http://dx.doi.org/10.13039/501100011033 and by the European Regional Development Fund ERDF "A Way of Making Europe"